PEMBENTUKAN BUAH TERUNG (Solanum melongena L.) PARTENOKARPI MELALUI APLIKASI BERBAGAI KONSENTRASI GIBERELIN - Zainal, Abdullah Rahman (JSTT, 2015)
Parthenocarpy on plant can be produced through a number of approaches, for example via application of gibberellin on the flowers of plant. The aim of this experiment was to investigate the production of parthenocarpy on the eggplant via application of various gibberellin concentrations. This experiment was conducted on the farmer’s land in Lasoani village, Palu city, Central Sulawesi,from December 2014 to April 2015. This experiment used Randomized Block Design with treatments tested namely concentration of gibberellin consisted of four levels, including without gibberellin application, application of gibberellin with 0.1%; 0.2% and 0.3% per flower. Each treatment used five replications, and therefore there were 20 experimental units used.Furthermore, each experimental unit utilized two flowers and there were 40 flowers used as experimental object. Variables observed consisted of weight, length and diameter of eggplant fruits as well as the number of seeds formed. Results of this experiment indicated that the application of gibberellin had a significant effect on the parthenocarpy of eggplants. Eggplants applied with gibberellin at the concentrations of 0.1% - 0.3% resulted in parthenocarpy, but weight, length and diameter per eggplant only ranged from 32.76 g to 53.60 g; 6.94 cm to 9.30 cm; and 3.30 cm to 4.60 cm, respectively; whilst eggplants formed without application of gibberellin produced up to 221 seeds with weight, length and diameter per eggplant reached 162.32 g; 21.20 cm; and 5.12 cm, respectively.